Lymphadenopathy in Children and Young People. Issue 2 (February 2016) - Hambleton, Laura; Sussens, Jill; Hewitt, Martin
Abstract: Enlargement of the lymph nodes is part of the normal immune response of children. Nonetheless, as a sign or symptom it frequently causes concern to parents. Although many serious conditions can present with significant lymph node enlargement, most children will present with a more benign pathology. Attempting to distinguish between the two is the challenge for paediatricians and the value and extent of investigating needs careful consideration. This article offers practical advice in how to approach a child presenting with an enlarged lymph node.